PASCASARJANA IAIN SYEKH NURJATI CIREBON GENEALOGI DAN PENGEMBANGANNYA - A. R. Idham Kholid (LP2M IAIN Syekh Nurjati Cirebon, 2012)
This study aimed to describe the Graduate Program IAIN Sheikh Nurjati Cirebon, the dynamic development of programs and institutions. This study used a qualitative approach, data gathering methods such as depth interviews, observation and document study. Sources of primary data in this study is the program staff, program development documents and institutions of Graduate Program IAIN Sheikh Nurjati Cirebon. Secondary data sources are other documents that are not directly associated with developing Masters IAIN Sheikh Nurjati Cirebon. The results of this study are: 1) Graduate Program IAIN Sheikh Nurjati formally established in 2004 and started college in the academic year 2005/2006. The inauguration was done after efforts include planning (1994), a feasibility study (1998), and cooperation with the Graduate Program IAIN Sunan Gunungjati Bandung and University of Muhammadiah Yogyakarta eshtablished during that time. 2) Scientific program development efforts in the Graduate IAIN Sheikh Nurjati Cirebon which include facilitation lecturer in post-doctoral programs, short courses to some countries, training of students, providing lecturers from outside the campus, and the cooperation with other Graduate Program agencies. 3) Institutional development efforts through enhancing the proposal and plans the status of IAIN to UIN Sheikh Sheikh Nurjati Cirebon and establishing Doctoral Program (S3).